THE USAGE OF HORSE SAYINGS AND IDIOMS IN COMMUNICATION - Аdinazarov Uktam Kushokovich (Galaxy International Interdisciplinary Research Journal, 2023)
The article analysis of idioms are common phrases or expressions in a language that has a figurative meaning rather than a literal one. In other words, the meaning of an idiom cannot be deduced by looking at the individual words in the phrase.